TENSES IN ENGLISH: COMPARING PRESENT SIMPLE AND PRESENT CONTINIOUS. - Tojimamatova Mashhuraxon,; Shakhlo Karimjonova, (Ustozlar uchun, 2025)
The topic "Tenses in English: Comparing Present Simple and Present Continuous" focuses on two of the most commonly used tenses in English grammar. This article compares their structures, time expressions, and typical usage in daily communication.Understanding the differences between these tenses helps learners speak and write more accurately. The article includes practical examples and common mistakes to support effective learning.